2019
DOI: 10.3899/jrheum.190261
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Utility of Cardiovascular Risk Prediction Algorithms in Inflammatory Rheumatic Diseases: A Systematic Review

Abstract: Objective.We performed a systematic review of the literature to describe current knowledge of cardiovascular (CV) risk prediction algorithms in rheumatic diseases.Methods.A systematic search of MEDLINE, EMBASE, and Cochrane Central databases was performed. The search was restricted to original publications in English, had to include clinical CV events as study outcomes, assess the predictive properties of at least 1 CV risk prediction algorithm, and include patients with rheumatoid arthritis (RA), ankylosing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 60 publications
1
34
0
3
Order By: Relevance
“…In one Canadian cohort study, the relative risk was 10.1 for MI and 7.9 for stroke even after controlling for traditional Framingham risk factors (2). More recently, a systematic review of risk algorithms in rheumatic diseases found that most models underestimated the cardiovascular risk in SLE and rheumatoid arthritis (RA) (6). The few studies that examined the addition of biomarkers to a traditional risk factor panel in patients with rheumatic disease have largely demonstrated no improvement in predictive capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In one Canadian cohort study, the relative risk was 10.1 for MI and 7.9 for stroke even after controlling for traditional Framingham risk factors (2). More recently, a systematic review of risk algorithms in rheumatic diseases found that most models underestimated the cardiovascular risk in SLE and rheumatoid arthritis (RA) (6). The few studies that examined the addition of biomarkers to a traditional risk factor panel in patients with rheumatic disease have largely demonstrated no improvement in predictive capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Disappointingly, this is also true for the long‐term prediction for adverse clinical events because established risk models such as Systematic Coronary Risk Evaluation score, Framingham Risk Score, Reynolds risk score, generally and largely underestimate CV risk . Recently, Colaco et al performed a systematic review of the literature to describe current knowledge of CV risk prediction algorithms in rheumatic diseases. They confirmed that general risk algorithms mostly underestimate and at times overestimate cardiovascular risk in rheumatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…To study if UCP1 transcription contributes to CV morbidity, we estimated the risk to develop or die of CV disease by using the Pocock’s and Framingham risk models [ 31 , 32 ]. As a consequence of adverse metabolic profile and serum lipid levels, both UCP1+ groups had somewhat higher CV risk compared to other patients.…”
Section: Resultsmentioning
confidence: 99%
“…Estimation of CV risk in patients with RA often meets difficulties. Traditional prediction models provide only partial explanation to the well-documented premature CV mortality in RA patients [ 32 ]. Persistent disease activity and excess of inflammation initiated by cytokines has been postulated central for development of vascular pathology in RA [ 33 ].…”
Section: Discussionmentioning
confidence: 99%